Impact of Visual Impairment on Audiovisual Intelligibility in Noise in Presbycusis Patients - Hee, Alexis; Vannson, Nicolas (Canadian acoustics / Acoustique canadienne)

(untitled) (Association canadienne d’acoustique / Canadian Acoustical Association, 2025)
The main goal of this study was to investigate how visual impairment affects speech intelligibility in noisy environments, comparing individuals with normal hearing and those with presbycusis using bilateral hearing aids. Participants underwent an audiovisual FraMatrix test under different visual acuity conditions. The study found a significant reduction in audiovisual intelligibility in noise as visual acuity worsened. These findings underscore the importance of addressing both hearing and vision impairments in clinical practice to enhance patient well-being and reduce social isolation